2020
DOI: 10.1002/alz.047420
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Alzheimer's disease: a review of long‐term episodic memory encoding and retrieval fMRI studies

Abstract: Background Many risk factors have been identified that predict future progression to Alzheimer’s disease (AD). However, clear links have yet to be made between these risk factors and how they affect brain functioning in early stages of AD. Method We conducted a narrative review and a quantitative analysis to better understand the relationship between nine categories of AD risk (i.e., brain pathology, genetics/family history, vascular health, head trauma, cognitive decline, engagement in daily life, late‐life d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, a signi cant difference in alerting function was observed between the NS and non-NS groups but not healthy controls. Age has been shown to be associated with alterations in alerting function [9,24] , and has been identi ed as a risk factor for HIV-negative patients with NS in our previous study [25] ; thus, we further employed MANOVA with Bonferroni post-hoc test to determine whether patients with NS still displayed less e cient orienting and alerting attention functions. The ndings indicated that early forms of NS may be associated with a speci c structural impairment of the brain networks related to localization or alerting function rather than executive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a signi cant difference in alerting function was observed between the NS and non-NS groups but not healthy controls. Age has been shown to be associated with alterations in alerting function [9,24] , and has been identi ed as a risk factor for HIV-negative patients with NS in our previous study [25] ; thus, we further employed MANOVA with Bonferroni post-hoc test to determine whether patients with NS still displayed less e cient orienting and alerting attention functions. The ndings indicated that early forms of NS may be associated with a speci c structural impairment of the brain networks related to localization or alerting function rather than executive function.…”
Section: Discussionmentioning
confidence: 99%
“…The attentional network test (ANT) software, designed by Fan et al [8] , is a reliable and simple tool to take data for assessing attention de cits from children, patients and animals. The ANT has been widely used to explore the detailed attentional characteristics of individuals with neuropsychiatric disorders, such as attention-de cit/hyperactivity disorder, schizophrenia, and Alzheimer's disease [9][10][11] ; however, there is no report about the relationships between NS and the three attention networks. Studies on cognitive decline in patients with NS mainly employed the Mini-Mental State Examination (MMSE) or the Montreal Cognitive Assessment to evaluate general or extensive cognitive impairment [12][13][14] , while MMSE is sometimes di cult to identify NS patients with speci c domain or earlier cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%